2022
DOI: 10.33899/rdenj.2022.129402.1086
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Type and Concentration of Different Additives on the Water Sorption of Denture Base Resin

Abstract: Aims:To evaluate the effect of incorporation of different types and concentrations of additives on water sorption denture base acrylic resin. Materials and Methods: Heat polymerized acrylic resin samples were prepared and divided into two groups; control group (without additives) and experimental group (with additives). The additives were three types of polymers (Styrene Butadiene Rubber (SBR), Poly Ethylene Glycol (PE) and Poly Urethane (PU)) being added with three concentrations 1%, 3% and 5%. SPSS Version 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The incorporation of the recycled acrylic resin into the heat cured denture base resin improved its hardness (Table 1 ), which is consistent with the results obtained by Salim and Muhsin ( 2020 ), who concluded that the incorporation of a recycled polyether ether ketone polymer improved the hardness of the denture resin. The enhanced hardness could be attributed to the improved degree of conversion, high crystallinity, and/or decreased porosity of the resulting composite polymer (Dagdiya et al, 2019 ; Elboraey et al, 2016 ; Mohammed & Hasan, 2022b ), or it might be due to the decrease in the residual monomer content (Ajay et al, 2020 ). The highest hardness was recorded by adding 5% recycled acrylic resin.…”
Section: Discussionmentioning
confidence: 99%
“…The incorporation of the recycled acrylic resin into the heat cured denture base resin improved its hardness (Table 1 ), which is consistent with the results obtained by Salim and Muhsin ( 2020 ), who concluded that the incorporation of a recycled polyether ether ketone polymer improved the hardness of the denture resin. The enhanced hardness could be attributed to the improved degree of conversion, high crystallinity, and/or decreased porosity of the resulting composite polymer (Dagdiya et al, 2019 ; Elboraey et al, 2016 ; Mohammed & Hasan, 2022b ), or it might be due to the decrease in the residual monomer content (Ajay et al, 2020 ). The highest hardness was recorded by adding 5% recycled acrylic resin.…”
Section: Discussionmentioning
confidence: 99%